2022
DOI: 10.1038/s41467-022-32614-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric 1,4-functionalization of 1,3-enynes via dual photoredox and chromium catalysis

Abstract: The merger of photoredox and transition-metal catalysis has evolved as a robust platform in organic synthesis over the past decade. The stereoselective 1,4-functionalization of 1,3-enynes, a prevalent synthon in synthetic chemistry, could afford valuable chiral allene derivatives. However, tremendous efforts have been focused on the ionic reaction pathway. The radical-involved asymmetric 1,4-functionalization of 1,3-enynes remains a prominent challenge. Herein, we describe the asymmetric three-component 1,4-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 79 publications
2
20
0
Order By: Relevance
“…Wang et al, in 2022, reported an asymmetric 1,4-difunctionalization of 1,3-enynes using dual photoredox and Cr catalysts. The reaction of 1,3-enynes with aldehydes and DHP esters in the presence of CrCl 2 , 4CzIPN and chiral ligand under the radiation of blue LEDs afforded chiral allenols 41 in moderate to good yields with high enantioselectivities ( Scheme 40 ) [ 75 ]. The reaction mechanism suggests that isopropyl radical generated from DHP ester assisted adds to 1,3-enyne to provide propargyl radical M-87 followed by trapping with Cr II L to form the propargyl chromium M-88 and then chiral intermediate M-89 after nucleophilic addition to benzaldehyde.…”
Section: 14-difunctionalization Reactionsmentioning
confidence: 99%
“…Wang et al, in 2022, reported an asymmetric 1,4-difunctionalization of 1,3-enynes using dual photoredox and Cr catalysts. The reaction of 1,3-enynes with aldehydes and DHP esters in the presence of CrCl 2 , 4CzIPN and chiral ligand under the radiation of blue LEDs afforded chiral allenols 41 in moderate to good yields with high enantioselectivities ( Scheme 40 ) [ 75 ]. The reaction mechanism suggests that isopropyl radical generated from DHP ester assisted adds to 1,3-enyne to provide propargyl radical M-87 followed by trapping with Cr II L to form the propargyl chromium M-88 and then chiral intermediate M-89 after nucleophilic addition to benzaldehyde.…”
Section: 14-difunctionalization Reactionsmentioning
confidence: 99%
“…Very recently, Wang's group developed the cooperative photoredox and chromium catalyzed asymmetric 1,4-functionalization of 1,3-enynes, leading to chiral allenols 83 possessing axial and central chiralities in good results (Scheme 19). [34] A putative mechanism is outlined in Scheme 19. It was reasoned that the excited photocatalyst was quenched by the DHP ester 81 a to generate the reduced photocatalyst, the isopropyl radical 32 a and pyridinium 84.…”
Section: Metallaphotoredox Catalyzed Reactions Involving Allenyl Radi...mentioning
confidence: 99%
“…In 2022, the group of Xiao [9] , Li [10] , and Shi [11] independently realized Co/PC dual-catalyzed or Nicatalyzed reductive coupling of aryl halides with aldehydes. With the significant achievement, the simultaneous construction of multiple chiral elements [12] still remains elusive, especially for biaryl axially chiral secondary alcohol.…”
Section: Introductionmentioning
confidence: 99%